1969
DOI: 10.1090/s0002-9904-1969-12248-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in $M \times N$ with $\pi _1 M \ne 1$

Abstract: The case m -2k appears to be easier to handle, since the obstruction is the intersection form, which is just the ®-product of the form on M and the form on N, and is homologically defined. The self intersection form does introduce a complication, at least if k is odd. In any case we concentrate here on m = 2k + l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The pH of the buffer is critical since the degree of binding is known to vary with pH * Correspondence. (Williamson, 1969), this may also account for some of the variation in previously determined values (Table l), consequently the buffer used was at physiological pH since calcium citrated-plasma was used, Caz+ variations were not considered likely to affect the results. Preliminary studies showed that, with shaking, equilibrium was achieved between 48 and 72 h and that no dilution of the plasma occured and that the pH at equilibrium was 7.4.…”
mentioning
confidence: 96%
“…The pH of the buffer is critical since the degree of binding is known to vary with pH * Correspondence. (Williamson, 1969), this may also account for some of the variation in previously determined values (Table l), consequently the buffer used was at physiological pH since calcium citrated-plasma was used, Caz+ variations were not considered likely to affect the results. Preliminary studies showed that, with shaking, equilibrium was achieved between 48 and 72 h and that no dilution of the plasma occured and that the pH at equilibrium was 7.4.…”
mentioning
confidence: 96%
“…I(a)=0 if m^O (mod 4) and 1(a) = Index P for any PGa if m = 0 (mod 4), in which case the index of P is the index of the quadratic form (x\Jy) [P] on H m/2 (P; Q). Williamson [8] has shown that for n odd and m even, PROOF. Let P be a simply-connected representative of a.…”
Section: That Is If (X N Dx) Is a Manifold If $ Is A Vector Bundlmentioning
confidence: 99%